1979
DOI: 10.1111/j.1600-0587.1979.tb00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and annual variations in the prevalence of blood parasites in cyclic species of small rodents in Norway with special reference to Clethrionomys glareolus

Abstract: An investigation of the blood parasites of Clethrionomys glareolus, Microtus agrestis and Apodemus sylvaticus from southern Norway revealed four genera, Trypanosoma, Babesia, Hepatozoon and Grahamella. C. glareolus and M. agrestis harbored all four genera, but Hepatozoon was not detected in A. sylvaticus. Babesia was fairly common in M. agrestis but rare in the other rodents. The peak prevalence of Grahamella and Hepatozoon in C. glareolus occurred in early summer whereas trypanosomes peaked near the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
5
21
0
Order By: Relevance
“…Our results are in accordance to data from former Czechoslovakia, Austria and Great Britain (Šebek 1975, Šebek et al 1980, Frank 1978, Healing 1981, Turner 1986), but higher than from Norway (0-16.7% in summer -Wiger 1979). However, the infection with Herpetosoma trypanosomes depends on season (Turner 1986, Karbowiak andWita 2001).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are in accordance to data from former Czechoslovakia, Austria and Great Britain (Šebek 1975, Šebek et al 1980, Frank 1978, Healing 1981, Turner 1986), but higher than from Norway (0-16.7% in summer -Wiger 1979). However, the infection with Herpetosoma trypanosomes depends on season (Turner 1986, Karbowiak andWita 2001).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of T. microti was higher in root vole from Białowieża Forest (21.4-50.0%) than those noted for field vole (0.9-12.8% - Baker et al 1963, Šebek 1975, Healing 1981 and common vole Microtus arvalis (9.0% - Pawelczyk et al 2004). However, some authors showed the between-year variability in prevalence of this parasite (Wiger 1979, Pawelczyk et al 2004.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Seasonal (Wiger 1979, Turner 1986) and annual (Healing 1981) differences in the occurrence of blood forms of Hepatozoon have previously been reported from rodents in northern and Central Europe. In the present study, lung meronts were common in C. glareolus in all seasons (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports of Hepatozoon infections in small mammals from northern Europe (Tadros, cited in Killick-Kendrick 1974, Wiger 1979, Soveri et al 2000. In this paper we report prevalence and distribution data of Hepatozoon infections of small rodents from Finland and some other areas in northern Europe.…”
mentioning
confidence: 99%